2010
DOI: 10.3233/nre-2012-0731
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of inpatient rehabilitation of patients with multiple sclerosis

Abstract: Background: Several trials have demonstrated improved outcomes following inpatient rehabilitation for Multiple Sclerosis patients. Two populations were studied: patients in relapse and patients with no active medical problems recruited from the community. In every day practice, most admissions for MS inpatient rehabilitation aim to improve function following sudden deterioration. The outcomes of inpatient rehabilitation for this population were never studied. Method: Retrospective case note analysis of consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The impact of the disease duration is somewhat contradictory. In the study of Gaber et al (2010), no relationship was found between the disease duration and the achievement of rehabilitation goals. In this study, the assessment of benefit was made based on the achievement of 2013) patients with a longer disease duration had a poorer response to rehabilitation, that corresponds with finding of our study.…”
Section: Discussionmentioning
confidence: 94%
“…The impact of the disease duration is somewhat contradictory. In the study of Gaber et al (2010), no relationship was found between the disease duration and the achievement of rehabilitation goals. In this study, the assessment of benefit was made based on the achievement of 2013) patients with a longer disease duration had a poorer response to rehabilitation, that corresponds with finding of our study.…”
Section: Discussionmentioning
confidence: 94%
“…So although hospitalisation rates have decreased over time, it appears that those individuals who are hospitalised are sicker, and require more complex care 13. It is also possible that some individuals with MS remain in hospital longer as they wait for placement in a long-term care facility, or are receiving inpatient rehabilitation 36…”
Section: Discussionmentioning
confidence: 99%
“…Commonly cited benefits following inpatient rehabilitation include decreased fatigue, improved walking speed, and improved quality of life in MS patients [14,15]. Mobility is the most frequently reported area of improvement for patients with MS following a course of inpatient rehabilitation; however, baseline mobility is the most important predictive factor as to whether a patient will attain mobility goals [16][17][18][19]15]. Shorter disease course, longer rehabilitation length of stay (LOS), female sex, and relapsing subtype may be associated with better rehabilitation outcomes [20].…”
Section: Introductionmentioning
confidence: 99%